2017
DOI: 10.1017/s1368980017000118
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with high consumption of soft drinks among Australian secondary-school students

Abstract: High soft drink consumption clusters with other unhealthy lifestyle behaviours among Australian secondary-school students. Interventions focused on reducing the availability of soft drinks (e.g. increased taxes, restricting their sale in schools) as well as improved education on their harms are needed to lower adolescents' soft drink intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
93
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 42 publications
17
93
3
4
Order By: Relevance
“…A similar trend was observed in Australia [16]. Studies on models of nutrition have also shown increased consumption of coffee among adolescents.…”
Section: Figure 1 Body Mass Indexsupporting
confidence: 76%
See 2 more Smart Citations
“…A similar trend was observed in Australia [16]. Studies on models of nutrition have also shown increased consumption of coffee among adolescents.…”
Section: Figure 1 Body Mass Indexsupporting
confidence: 76%
“…A higher number of more active subjects had regular 4-5 meals a day, including breakfast, which may prove the respondents' awareness of healthy behaviours [12]. Our survey conducted in a group of English-speaking students revealed an alarmingly low consumption of fruit and vegetables, also reported by other authors [16]. Less than 50% of students include these important products in their everyday diet.…”
Section: Figure 1 Body Mass Indexsupporting
confidence: 67%
See 1 more Smart Citation
“…Based on factor analysis, a composite scale combined ratings of “agreed” for two or more stereotypes . Respondents who reported they drank SSBs one or more times in the last week were classified as “weekly SSB consumers” and those who drank SSBs four or more times in the last week were classified as “frequent SSB consumers.”…”
Section: Methodsmentioning
confidence: 99%
“…Of note is that males reported, in all analyses, a significantly higher frequency of soft drink consumption compared with females (per school type, per age, and including all ages). This higher consumption of soft drinks in males has been reported several times [Kassem and Lee, 2004;Pinket et al, 2016;Scully et al, 2017] and suggests that genderspecific interventions should be applied for the prevention of this high consumption of soft drinks.…”
Section: Discussionmentioning
confidence: 59%